(untitled) (Revista da Faculdade de Direito, Universidade de São Paulo, 2023)
Distribution of ineffective medicines for medical treatment of COVID-19 in Brazil has led to societal division over how standards of scientific safety shall anchor decision made by national agencies faced to a complex and globalized regulatory framework. In this paper, I argue that this circumstance has exposed a tension between a nuclear pattern of administrative discretion to conceive public policies and a peripheral reasoning of scientific safety proper of risk society. By doing so, I address State’s understanding to question if such tension means crisis of the State or its technical adaptation. For this purpose, I raise traditions of thought that regard the State as an expression of sovereign unit of will, as well as those which held the State as the monopoly of use of force, including symbolic force, so that it edifies the sense of official and legitimation. I conclude that regulation and the way by which States have led with risk compress administrative discretion and the sense of political representation. However, the perception of States’ crisis depends on the view of its concept and functioning.